2017
DOI: 10.1001/jama.2016.18663
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variations and Temporal Trends in Cesarean Delivery Rates in China, 2008-2014

Abstract: veruse of cesarean delivery can jeopardize maternal and child health. 1,2 Concerns about "alarming" 3 rates in China increased after the World Health Organization (WHO) 4 reported that 46.2% of births were delivered by cesarean in the years 2007 and 2008, based on an analysis of 14 541 deliveries in 21 hospitals in 3 provinces. With a population of approximately 1.37 billion in 2014, China's health care use is of substantial global interest. Over the past 2 decades, the nation has invested in improving materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
264
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 256 publications
(289 citation statements)
references
References 11 publications
18
264
4
3
Order By: Relevance
“…It also contributes to reduce the risk of cesarean delivery. The rate of cesarean delivery increased by years from 28.8% to 34.9% between 2008 and 2014 in China [6]. It was higher than the rate in this study.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…It also contributes to reduce the risk of cesarean delivery. The rate of cesarean delivery increased by years from 28.8% to 34.9% between 2008 and 2014 in China [6]. It was higher than the rate in this study.…”
Section: Discussioncontrasting
confidence: 66%
“…For example, it was proved cesarean delivery was significantly associated with risk of autism spectrum disorder for each week of gestation, from week 36 to 42compared with vaginal delivery [7]. Study results also showed there was no increase in maternal or perinatal mortality in 4 super cities with the largest decreases of cesarean delivery rate [6].…”
Section: Discussionmentioning
confidence: 92%
“…Research evidence suggests that postpartum and intrapartum insertion of IUDs is feasible and does not interfere with normal uterine involution 23. Hence, to insert IUDs immediately after the placenta has been delivered should be strongly recommended as best practice in China, as the overall caesarean prevalence is 34.9%24 and 43.4% in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…The recent increase in cesarean section (CS) rates (i.e. the number of cesarean deliveries performed per 100 live births) is a global health issue, especially in middle and high‐income countries . Although CS is an effective procedure to prevent maternal and perinatal morbidity and mortality, it may be accompanied by surgical complications (e.g.…”
Section: Introductionmentioning
confidence: 99%